Maternal Breastfeeding Methods, Breastmilk-Derived Antibodies and Cells Concentrations and Their Impact on Infant Morbidity: Results from a Prospective Cohort in Southern Benin - LOKOSSOU, GATIEN; ADJEVI, Pierre Bessan; MALADE, Omar; BABA MOUSSA, Lamine (My University, 2022)
Breastfeeding is associated with long-term well-being including low risks for infectious diseases and non-infectious diseases such as asthma, cancer, autoimmune diseases and obesity during childhood. However, very few studies assessed the real-impact of different methods of breastfeeding on infant morbidity in low-income countries such as Benin. Our study aimed to evaluate the dynamic change of immune components and the impact on infant morbidity among Beninese children population. Seventy-six children and their mothers were enrolled in colostrum, transitional and mature milk groups at the District Hospital of Comè in Bénin. Breast milk samples were collected one-time from mothers to assess total IgA, IgG and IgM and leukocytes by using spectrophotometry and level of microscopy, respectively. Mean or proportion comparisons were appreciated using a Mann-Whitney or Fisher’s exact tests, when appropriate. Forty (54.63%), six (7.89%) and thirty (39.47%) mother-infant pairs were enrolled in colostrum, transitional and mature milk groups respectively. The total number of leucocytes and antibodies were different in colostrum, transitional and mature milk. The prevalence of breastfeeding was 90.79% (n=69) in the population with 69.74% (n=53) of exclusive breastfed. Forty-five infants (84.91%) among exclusively breastfed infants were healthy whereas 4 (25%) among mixed breastfed infants and 4 (57.14%) among formula group were healthy (p=0.001). The total leucocytes count and IgA, IgG and IgM concentration decreases from colostrum through transition milk to mature milk. Our data showed a prevalence of exclusive breastfeeding which is associated to a positive clinical outcome on infant’s health. We have also confirmed decrease of antibodies and leucocytes during the maturation of breast milk.
Keywords: Human breast milk; Breastfeeding; Infant health; Immunity; Antibodies